2022
DOI: 10.5045/br.2022.2022038
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in treatments of adult immune thrombocytopenia

Abstract: Immune thrombocytopenia (ITP) is isolated thrombocytopenia characterized by autoimmune-mediated disruption of platelet without other etiologies. Treatments for chronic ITP consist of corticosteroids, intravenous immunoglobulins, anti-D immunoglobulin, rituximab, thrombopoietin receptor agonists, immunosuppressants and splenectomy. Although current therapies are effective in over two-thirds of patients, some patients are refractory to therapies or fail to achieve long-term responses. Recently, great advance has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…Categorized based on the antigenic target site, these antibodies include various types such as anti-GPIa/IIa, anti-GPIbα, anti-GPIb/IX, and anti-GPIIb/IIIa antibodies ( 53 , 54 ). In the majority of ITP patients, anti-GPIIb/IIIa antibodies are present in 70% to 80% of cases, while anti-GPIbα antibodies are found in 20% to 40% of cases.…”
Section: The Process Of Generation Of Platelet Desialylationmentioning
confidence: 99%
“…Categorized based on the antigenic target site, these antibodies include various types such as anti-GPIa/IIa, anti-GPIbα, anti-GPIb/IX, and anti-GPIIb/IIIa antibodies ( 53 , 54 ). In the majority of ITP patients, anti-GPIIb/IIIa antibodies are present in 70% to 80% of cases, while anti-GPIbα antibodies are found in 20% to 40% of cases.…”
Section: The Process Of Generation Of Platelet Desialylationmentioning
confidence: 99%
“…2 EP, ROMI, and avatrombopag are currently approved for the treatment of persistent or chronic ITP, unresponsive to previous first-line agents or splenectomy. 9 Several studies have reported overall response rates of 60 to 90% in ITP patients receiving TPO-RAs. 9 Results of increased efficacy in ITP patients along with understanding TPO's effects on HSCs gave rise to employment of TPO-RAs in a variety of thrombocytopenic settings.…”
Section: Introductionmentioning
confidence: 99%
“…9 Several studies have reported overall response rates of 60 to 90% in ITP patients receiving TPO-RAs. 9 Results of increased efficacy in ITP patients along with understanding TPO's effects on HSCs gave rise to employment of TPO-RAs in a variety of thrombocytopenic settings. 2 EP has been shown effective in the management of thrombocytopenia related to hepatitis C virus (HCV) infection, thus allowing initiation and maintenance of interferon-based therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Thrombopoietin receptor agonists (TPO-RAs) are second-line drugs used to treat ITP. They can bind to and activate thrombopoietin receptors on the membranes of megakaryocytes in the bone marrow, thus promoting megakaryocyte maturation and increasing platelet production ( 4 , 5 ). Currently, TPO-RAs that have been approved by China, the US and the EU for the clinical treatment of ITP include romiplostim, eltrombopag, avatrombopag and hetrombopag ( 5 , 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…They can bind to and activate thrombopoietin receptors on the membranes of megakaryocytes in the bone marrow, thus promoting megakaryocyte maturation and increasing platelet production (4,5). Currently, TPO-RAs that have been approved by China, the US and the EU for the clinical treatment of ITP include romiplostim, eltrombopag, avatrombopag and hetrombopag (5,6). Over the Thrombopoietin receptor agonists use and risk of thrombotic events in patients with immune thrombocytopenic purpura: A systematic review and meta-analysis of randomized controlled trials past decade, TPO-RAs have become increasingly common for treating ITP.…”
Section: Introductionmentioning
confidence: 99%